Perancangan Sistem Informasi Akuntansi Persediaan Barang Pada Toko Jabat - Ade Dwi Putra; Lomo Maykel Purba; Nuralia Nuralia (Journal of Engineering and Information Technology for Community Service, 2022)
The process of registering goods is very important because we need to know when goods enter and leave, and when checking, we need to know the existing stock. The current system running at Jabat stores has many shortcomings and weaknesses, including the recording of receipts and problems at Jabat stores is not yet fully electronic, so inventory management is slow and often incomplete. Common errors such as number typos or missing data. Reports that are still manual greatly affect the company's performance and have not been able to meet all company needs. The application is expected to help and facilitate the work of the Administration in managing the list of goods reports, incoming goods reports, outgoing goods reports, and inventory reports as well as minimizing errors in processing these reports